2017
DOI: 10.1126/sciadv.1700921
|View full text |Cite
|
Sign up to set email alerts
|

A spongy nickel-organic CO 2 reduction photocatalyst for nearly 100% selective CO production

Abstract: A spongy nickel-organic photocatalyst with nearly 100% selective CO2 to CO conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
95
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(99 citation statements)
references
References 58 publications
4
95
0
Order By: Relevance
“…Thet hickness of m-NiAl-LDH is larger than the theoretical value of LDH monolayer (0.48 nm), which is mainly due to the presence of adsorbed species (such as charge-balancing anion and formamide). [9,24] Additional control experiments on adjusting the amount of Ru(bpy) 3 Cl 2 ·6 H 2 Oa nd CH 3 CN:TEOA:H 2 Ow ere also optimized (Supporting Information, Figures S7, S8). Above all, it can be concluded that as eries of NiAl-LDH with the thickness ranging from 27 nm (b-NiAl-LDH), to 5nm( f-NiAl-LDH), and to 1nm(m-NiAl-LDH) were prepared.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thet hickness of m-NiAl-LDH is larger than the theoretical value of LDH monolayer (0.48 nm), which is mainly due to the presence of adsorbed species (such as charge-balancing anion and formamide). [9,24] Additional control experiments on adjusting the amount of Ru(bpy) 3 Cl 2 ·6 H 2 Oa nd CH 3 CN:TEOA:H 2 Ow ere also optimized (Supporting Information, Figures S7, S8). Above all, it can be concluded that as eries of NiAl-LDH with the thickness ranging from 27 nm (b-NiAl-LDH), to 5nm( f-NiAl-LDH), and to 1nm(m-NiAl-LDH) were prepared.…”
Section: Resultsmentioning
confidence: 99%
“…[1] To date,v arious approaches including photocatalytic reduction, [2] electrochemical reduction, [3] photoelectrochemical reduction, [4] and reverse water-gas shift [5] have been demonstrated to be efficient for converting CO 2 into value-added products.A mong these approaches,p hotocatalytic CO 2 reduction (CO 2 PR) is advantageous in using solar energy as ac lean and renewable energy source.I nt he last decades, great progress has been achieved in designing active catalysts for the reduction of CO 2 into important C1 chemicals such as CH 4 and CO. [2a,6] However,t he photocatalytic reaction usually occurs under ultraviolet (UV) light owing to the inefficiencyo fp hotocatalyst under lower photon energy, which limits the full usage of solar energy.M eanwhile,t he generation of H 2 from reduction of H 2 Owith photogenerated electron always competes with CO 2 PR and leads to ap oor selectivity of carbon product. [8] Zheng et al [9] achieved aselectivity of nearly 100 %inCO 2 PR to CO under visible light (l > 420 nm) by using aspongy Niorganic photocatalysts.X iong et al [10] developed an efficient CO 2 PR photocatalytic system with 100 %s electivity to CO and CH 4 by using Ni-doped CdS quantum dots under 400-470 nm. Recently,s ignificant progresses have been made to improve the activity for CO 2 PR under visible light.…”
Section: Introductionmentioning
confidence: 99%
“…This fact is more likely considering that the reduction of CO 2 in water is limited by its low solubility, which indirectly increases the probability for electrons to react with protons for HER rather than for both electrons and protons to reach CO 2 for CRR. Therefore, reaction selectivity is important in the case of CRR, where modifying the photocatalyst surface, altering the exposed facets, introducing new active sites, applying directional charge driving forces, etc., are subject to that reaction selectivity …”
Section: Spe For Energy Conversion and Environmental Treatmentmentioning
confidence: 99%
“…[13][14] These two factors greatly hamper the performance of semiconductor photocatalysts to reduce CO 2 . Indeed, a huge number of catalysts have been developed to work CO 2 photoreduction with considerable progress achieved, [15][16][17][18][19][20][21][22][23] the exploitation of new alternatives with highefficiency and stability, especially the candidates made of affordable elements, is still highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Nickel and cobalt species with rich redox states have been demonstrated to be active sites of photocatalysts, which can powerfully promote the separation and transfer of light-excited charges of CO 2 photoconversion catalysis. [18,[26][27][28][29][30][31] When the reduction reaction is further coupled with the protons, reinforced performance of CO 2 photoreduction can be achieved.…”
Section: Introductionmentioning
confidence: 99%